2021
DOI: 10.1038/s41598-021-92921-6
|View full text |Cite|
|
Sign up to set email alerts
|

The U-shaped association of serum iron level with disease severity in adult hospitalized patients with COVID-19

Abstract: Coronavirus disease 2019 (COVID-19) is an emerging infectious disease that leads to severe respiratory failure (RF). It is known that host exposure to viral infection triggers an iron-lowering response to mitigate pathogenic load and tissue damage. However, the association between host iron-lowering response and COVID-19 severity is not clear. This two-center observational study of 136 adult hospitalized COVID-19 patients analyzed the association between disease severity and initial serum iron, total iron-bind… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 18 publications
5
35
0
Order By: Relevance
“…It was speculated that lower serum iron and higher serum ferritin in male patients would be associated with more severe disease in male patients [ 13 ]. However, another study reported lower levels of serum iron and transferrin saturation in female patients than male patients [ 15 ]. Besides gender, age is another factor to consider in COVID-19.…”
Section: Overview Of Iron and Iron-related Proteins In Covid-19 Patientsmentioning
confidence: 99%
“…It was speculated that lower serum iron and higher serum ferritin in male patients would be associated with more severe disease in male patients [ 13 ]. However, another study reported lower levels of serum iron and transferrin saturation in female patients than male patients [ 15 ]. Besides gender, age is another factor to consider in COVID-19.…”
Section: Overview Of Iron and Iron-related Proteins In Covid-19 Patientsmentioning
confidence: 99%
“…We assessed sex specific summary-level data on iron status and COVID-19 outcomes and showed that there was some tendency that the effect of serum iron and TSAT was more pronounced among women compared with men. Another study looking at iron status at time of hospitalization for COVID-19 identified sex differences where female patients had significantly lower serum iron, TSAT and ferritin levels and higher TIBC levels compared to men, whereas the association with severity between serum iron and TSAT was observed in both sexes (15).…”
Section: Discussionmentioning
confidence: 99%
“…Genetically-predicted iron status may not perfectly reflect this time-varying exposure (51). The U-shaped risk relationship that has been proposed for the extremes of iron status (10, 15) might cause an attenuated association when evaluated in a linear model as in the two-sample MR methods. Non-linear MR methods could be more suitable to explore this U-shaped relationship but requires large GWAS with both measurements of iron biomarkers as well as the outcomes of interest (37).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations